Do Different Wheat Varieties Respond Differently to Nitrogen Rates in Terms of Grain Yield and Grain Protein Concentration in Kansas? - N. Giordano; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2021)
Nitrogen management in wheat can result in positive impacts on grain yield and grain protein concentration (GPC) if addressed correctly. The aim of this study was to compare whether different varieties responded differently in terms of grain yield and GPC to management of nitrogen (N) rate across different environments. Factorial field experiments were carried out in a split-plot design in four different Kansas locations to evaluate the combination of four N rates (whole plot, 0, 40, 80, and 120 lb N/a) and fourteen different commercially available winter wheat varieties (sub-plots). Grain yield and GPC were measured at harvest maturity. The grain yield average across all treatments at all locations was 50.3 bushels per acre, ranging from 33.6 to 84.9 bu/a depending on treatment and location. Mean GPC across all site-treatment combinations was 11.3%. There were significant interactions between environment and variety, and between environment and N rate for both grain yield and GPC, but not variety by N rate interaction. Different varieties provided to the highest yield and protein groups depending on location. Yield response to N was location-specific due to different amounts of soil NO3-N in the profile. In general, the highest GPC were obtained with the highest N rates in all locations except for one study site where 80 lb N/a sufficed. Results suggest that variety performance and optimum N rate that maximizes yield changed within the different environments, but the same N rate regime should be adopted across varieties.
Keywords: Triticum aestivum L.; wheat; nitrogen; wheat varieties